Malaysian urban poor adoption of e-government applications and their satisfaction - Shuib, Liyana; Yadegaridehkordi, Elaheh; Ainin, Sulaiman; Feng, Guangchao Charles (Cogent OA, 2019)
The aim of this research is to examine factors that influence citizens’ adoption of the e-government applications in Malaysia. In addition, their satisfaction is also analyzed. The research model was developed based on the integration of the Technology Acceptance Model and Diffusion of Innovation as well as trust in the government, information quality, computer self-efficacy, and customer satisfaction constructs regarding e-government applications in Malaysia. The data was collected using a Likert-scale questionnaire from 801 Malaysian urban poor citizens. Results revealed that compatibility, relative advantage, image, trust in the government, computer self-efficacy, and customer satisfaction have significant impacts on the use of e-government applications. In turn, customer satisfaction was itself positively influenced by the use of e-government applications. This research has provided in-depth understanding of critical factors in enhancing adoption and citizens’ satisfaction with e-government applications. © 2019, © 2019 The Author(s). This open access article is distributed under a Creative Commons Attribution (CC-BY) 4.0 license.